Paskeblomst - Concertos for organ and strings - Esquisses grégoriennes - Hakim, Naji; Komulainen, Petri; Lehtola, Jan; St. Michel Strings (Mikkeli, Finland) (Finland Alba Records, 2008)
Naji Hakim may be best-known as an organist and a composer of organ music; but, as this release makes clear, he also composed - and still does - orchestral music and concertos including one for violin and three for organ. The Second Organ Concerto is scored for organ and orchestra while the First and Third Concertos are scored for organ and strings. Påskeblomst (Easter Flower) for strings is a theme and variations on a hymn composed in 1910 by Carl Nielsen. In fact, it would probably be more appropriate to describe the various movements as free fantasias on Nielsens hymn tune. The music is by turns serious, lyrical, meditative and joyfully dance-like, particularly so in the last section. The whole amounts to a wonderful work, superbly written for strings, full of contrasts and of nicely judged string textures that sometimes bring Brittens equally imaginative Frank Bridge Variations to mind. It definitely deserves wider exposure. In the Concerto No.1 for Organ and Strings composed as a commission from the Dutch Orgelkring Heeswijk organ festival, the organ does not really stand out but is more like a primus inter pares sometimes playing a more orchestral part than a truly concerted one. The three movements are laid out in the traditional mould with two lively outer ones framing a slower, more meditative central Andante alluding to fragments of plainchant and Gregorian hymns. Improvising on plainchant hymn-tunes is part of any organists diet; and, as many other organist-composers before him, Hakim composed paraphrases on such hymn-tunes. His recent Esquisses Grégoriennes clearly belong to that tradition of improvisation. The unnamed annotator mentions that the Esquisses might be regarded as an organ mass in five movements : Nos autem (Introitus), Ave maris stella (Offertorium), Pater Noster (Elevation), Ave verum (Communion) and O filii et filiae (closing music). Whichever way you look at it, this set of improvisations is remarkably done and full of imagination. Hakim mentions Debussy, Stravinsky, Poulenc and even Gershwin as models for and influences on his music. However, Poulenc is the one that immediately comes to mind when listening to the Concerto No.3 for Organ and Strings although Hakims work is far from being a mere blue-print of Poulencs deservedly popular concerto. The outer movements quite often display that sort of nonchalance often associated with the French composer with dancing, carefree, catchy themes that stay with you once heard. The middle movement is a set of variations of texture rather than key on a Maronite melody. Hakims Third Organ Concerto is another marvellous piece and a most welcome addition to the repertoire. Incidentally this work is dedicated to Franz Hauk who recorded a number of rare works for organ and orchestra on the Guild label.
Keywords: 21st Century (2001-2100); Organ music; Orchestral music; Finland